Smile stimuli induce better performance in tests performed by children and adolescents practicing jiu-jitsu - María Merino-Fernández; Alfonso Lopéz Díaz-de-Durana; Lindsei Brabec Mota Barreto; Diego Ignacio Valenzuela Pérez; Ciro José Brito (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Aims: This study compared the performance of children and adolescents practicing jiu-jitsu when stimulated or not stimulated to smile before specific and non-specific physical tests. Methods: 268 children and adolescents (male=168) were measured in 5 tests (30” by 3’ interval) of which 3 were specific (4-Leg Exercise, Gyaku-tsuki test and O-soto-otoshi nage-komi test) and 2 non-specific (Side jumps and Burpees). These tests were carried out under two conditions: a) without prior stimuli; b) after joy stimuli. Results: There was an isolated effect of the pre-test intervention for non-specific tests, with better performance after joy stimuli (Side jumps: 35.8±13.3 vs. 30.1±11.1; Burpees: 16.1±5 .3 vs. 13.8±4.8 repetitions; p≤0.001 for both comparisons). There were also isolated effects of the pre-test intervention for the specific O-soto-otoshi nage-komi test and 4-Leg Exercise, where happiness stimuli resulted in better performance (O-soto-otoshi nage-komi test: 15.2±3.5 vs. 12.5 ± 3.7 repetitions; 4-Leg Exercise: 3.5±1.2 vs. 2.8±1.2 repetitions p≤0.001 for both comparisons). For the Gyaku-tsuki test, there was an interaction effect between intervention and age (p=0.02), where older children performed better. Conclusion: Stimulating emotions of happiness brings better performance in children and adolescents practicing jiu-jitsu regardless of gender and age, except for the Gyaku-tsuki test where older people tend to perform better.